Processed line aerogravity data over Wilkes Subglacial Basin region (2005/06 season) - Jordan, Tom; Ferraccioli, Fausto; Armadillo, Egidio; Bozzo, Emanuele (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
This data set contains aerogravity data collected during the WISE/ISODYN project. This collaborative UK/Italian project collected ~ 61000 line km of new aerogeophysical data during the 2005/2006 austral summer, over the previously poorly surveyed Wilkes subglacial basin, Dome C, George V Land and Northern Victoria Land. We present here the processed line aerogravity data collected using a LaCoste & Romberg air-sea gravity meter S83 mounted in the BAS aerogeophysically equipped Twin Otter aircraft. Data are provided as XYZ ASCII line data. : WISE-ISODYN aerogeophysics data presented in (Ferraccioli et al., 2009), further details on basic data acquisition are described in (Ferraccioli et al., 2007). The dataset available here includes channels from raw through to filtered and upward continued free air anomalies, where data was recoverable. Data processing steps are outlined below Processing steps: 1/ Calculate observed gravity. True spring tension (ST_real) is calculated from the posted spring tension (ST) correcting for the fact that for this survey the true spring tension approaches the posted value at 38 mGal per second. Beam velocity (Beam_vel) is derived from raw beam position (RB) assuming a centred difference approximation. Relative gravity (rec_grav) = (Spr_tens_real+((beam_vel)*k_fac)+CC)*scale_value, k_fac=30, meter scale value = 0.9966. Still readings (Still) are in mGal and were calculating assuming a 2nd order best fit to the approximately linear drift of the meter observed at the tie down points. Airborne absolute gravity values (Abs_grav) = Rec_grav - Still + Base 2/ Corrections to derive free air anomalies (disturbances). Vertical acceleration (VaccCor) is calculated as 2nd derivative of flight altitude (Height_WGS1984), with a 3 point mean filter applied after differencing to reduce short wavelength noise. Eotvos correction (EotvosCor) follows (Harlan, 1968). Latitude correction (LatCor) = 978.03185(1+0.005278895 sin2Lat- 0.000023462 sin4Lat) (IUGG 1967). Free air correction (FaCor) = 0.3086*Height_WGS1984. NOTE subsequent free air values are defined as gravity disturbances in geodesy, as they are referred to the ellipsoid (Hackney and Featherstone, 2003). Horizontal acceleration correction (HaccCor). For this survey the approximation of (Swain, 1996) was used, assuming a damping factor of 0.707, and a platform period of 4 minutes. 3/ Free air anomaly and filtering. Free air anomaly (Free_air) = Abs_grav-VaccCor+EotvosCor+FaCor-LatCor-(0.5*HaccCor) Filtered free air anomaly (FAA_filt) used 9 km 1/2 wavelength space domain kernel filter (Holt et al., 2006). Final free air data (FAA_clip) was produced by manually masking turns, start and end of lines, and other regions of noisy data. Upward continued free air anomaly (Faacont) was produced by upward continuing free air data from the collected flight altitude to 2800 m. Channel description: Basic Channels Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_name Line Number e.g. LW200.1:12 Lon Longitude WGS 1984, for processing see readme Lat Latitude WGS 1984, for processing see readme x x projected meters* y y projected meters* Height_WGS1984 Aircraft altitude (meters) in WGS 1984, for processing see location data page Raw gravity Channels ST Spring Tension (meter units) CC Cross Coupling (meter units) RB Raw beam position (Mv) XACC Cross axis accelerometer (Mv) LACC Long axis accelerometer (Mv) Still Airborne meter still reading value (mGal) Base Absolute gravity reference, from land gravity (mGal) Calculation Channels St_real True Spring tension value (meter units) Beam_vel Gravity meter beam velocity (Mv/sec) Rec_grav Recalculated relative gravity (mGal) Abs_grav Calculated absolute gravity (mGal) VaccCor Vertical acceleration correction EotvosCor Eotvos correction LatCor Latitude correction FaCor Free air correction HaccCor Horizontal acceleration correction Free air Channels Faa Un-filtered free air anomaly FAAup Upward continued free air anomaly to altitude 2800 m *Projected coordinates (x and y) are in Lambert conic conformal with two standard parallels defined as follows: Latitude of false origin: -74.018118 Longitude of false origin: 179 Latitude of 1st standard parallel -72.66666666667 Latitude of 2nd standard parallel -75.33333333333 False easting 1444000 False northing 1123000